2001
DOI: 10.2134/agronj2001.1200
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Yield Response to Reproductive Stage Soil‐Applied Nitrogen and Foliar‐Applied Boron

Abstract: from several sources, including mineralized soil organic matter, symbiotically fixed N, and N incorporated into Research on the effects of N and B applications on soybean [Glyplant tissue. Demand for seed N is highest from the R5 cine max (L.) Merr.] yield is limited. Experiments were conducted kg ha Ϫ1 applied from seedling emergence to R1 in-Holland Rd., Suffolk, VA 23437; and M.M. Alley, Dep. of Crop and creased yields by 720 kg ha Ϫ1 , averaged across all treat-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 32 publications
4
35
0
2
Order By: Relevance
“…The states were: Arkansas, Iowa, Illinois, Indiana, Kansas, Kentucky, Louisiana, Michigan, Minnesota, Missouri, Ohio, North Dakota, Nebraska, Oklahoma, Virginia, and Wisconsin. Raw data from many sources (Freeborn et al, 2001;Wortmann et al, 2012;Attia et al, 2015;Staton et al, 2011Staton et al, -2016Orlowski et al, 2016;Mourtzinis et al, 2017) as well as several sources of previously unpublished data were included in our analysis. The resultant database consisted of 5991 plot-specific yield data derived from a total of 207 environments (experiment × year).…”
Section: Data Descriptionmentioning
confidence: 99%
See 1 more Smart Citation
“…The states were: Arkansas, Iowa, Illinois, Indiana, Kansas, Kentucky, Louisiana, Michigan, Minnesota, Missouri, Ohio, North Dakota, Nebraska, Oklahoma, Virginia, and Wisconsin. Raw data from many sources (Freeborn et al, 2001;Wortmann et al, 2012;Attia et al, 2015;Staton et al, 2011Staton et al, -2016Orlowski et al, 2016;Mourtzinis et al, 2017) as well as several sources of previously unpublished data were included in our analysis. The resultant database consisted of 5991 plot-specific yield data derived from a total of 207 environments (experiment × year).…”
Section: Data Descriptionmentioning
confidence: 99%
“…Based on lack of response to supplemental N applications, Freeborn et al (2001) concluded that N supply through BNF and soil organic matter mineralization is sufficient for high soybean yields. However, BNF activity can be limited by a number of environmental conditions such as low soil moisture, extremes of soil pH and temperature, and soil compaction, any of which can result in insufficient N supply to the soybean plants (Purcell and King, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to provide soybeans with adequate N for maximum seed yield, producers have considered applying N fertilizer to their soybean crop. Previous studies have reported inconsistent responses of soybean seed yield to N fertilizer applications [6][7][8][9][10][11][12][13][14][15][16][17][18]. For instance, in the Southern US, no effect was reported in Texas [7] and Alabama [6].…”
Section: Introductionmentioning
confidence: 98%
“…Gan et al (2003) in China, indicated yield increases of 9 to 26% across three soybean genotypes when 50 kg N ha -1 were applied at R1 compared to non-fertilized soybean but no response if N was applied at R3 or R5. No response to N fertilization strategies are reported by Schmitt et al (2001;Minnesota), Freeborn et al (2001;Virginia), and Gutiérrez-Boem et al (2004; North of Buenos Aires Province) in well-nodulated high yielding soybean crops (>3.5 Mg ha -1 ).…”
mentioning
confidence: 95%
“…However, common yields in the region are limited to <3 Mg ha -1 (Calviño and Sadras, 1999;Calviño and Monzón, 2009) due to water stress during the seed fi lling period (R4-R6 stages). Reduced soil water availability (SWA) during soybean reproductive stages increases the yield gap by reducing the photosynthetic rate and the N assimilation rate (lower SNF and reduced soil N mineralization), and by increasing remobilization of plant C and N to the seeds with shortening of the reproductive stages and premature leaf senescence (De Souza et al, 1997;Freeborn et al, 2001;Purcell et al, 2004). Earlier studies in the southeast of Buenos Aires Province determined that if SWA during R4 to R6 stages drops below 60%, yield losses of 30% or more can be expected Calviño and Monzón, 2009).…”
mentioning
confidence: 99%